On the Frontline: Tracking Ocean Acidification in an Alaskan Shellfish Hatchery - Evans, Wiley; Mathis, Jeremy T.; Ramsay, Jacqueline; Hetrick, Jeff (PLOS ONE, 2015)
The invasion of anthropogenic carbon dioxide (CO2) into the ocean is shifting the marine carbonate system such that saturation states of calcium carbonate (CaCO3) minerals are decreasing, and this is having a detrimental impact on early life stages of select shellfish species. The global, secular decrease in CaCO3 saturation states is occurring on top of a backdrop of large natural variability in coastal settings; progressively shifting the envelope of variability and leading to longer and more frequent exposure to adverse conditions. This is a great concern in the State of Alaska, a high-latitude setting vulnerable to rapid changes in the marine carbonate system, where an emerging shellfish industry plans major growth over the coming decades. Currently, the Alutiiq Pride Shellfish Hatchery (APSH) in Seward, Alaska is the only hatchery in the state, and produces many shellfish species with early life stages known to be sensitive to low CaCO3 saturation states. Here we present the first land-based OA measurements made in an Alaskan shellfish hatchery, and detail the trends in the saturation state of aragonite (Ωarag), the more soluble form of CaCO3, over a 10-month period in the APSH seawater supply. These data indicate the largest changes are on the seasonal time scale, with extended periods of sub-optimal Ωarag levels (Ωarag < 1.5) in winter and autumn associated with elevated water column respiration and short-lived runoff events, respectively. The data pinpoint a 5-month window of reprieve with favorable Ωarag conditions above the sub-optimal Ωarag threshold, which under predicted upper-bound CO2 emissions trajectories is estimated to close by 2040. To date, many species in production at APSH remain untested in their response to OA, and the data presented here establish the current conditions at APSH as well as provide a framework for hatchery-based measurements in Alaska. The current and expected conditions seen at APSH are essential to consider for this developing Alaskan industry.